Effectiveness of Intravenous Ilomedin Infusion and Smoking Cessation in the Treatment of Acutely Symptomatic Buerger Disease. (February 2015) - Spanos, Kostas; Georgiou, Evangelia; Saleptsis, Vassileios; Athanasoulas, Athanasios; Sakkas, Lazaros; Giannoukas, Athanasios D.
We assessed the effectiveness of iloprost treatment in the management of symptomatic Buerger disease (BD) and assessed smoking cessation compliance, based on a single-center experience. Thirteen patients with BD were treated with sessions of intravenous (IV) Ilomedin infusion. At 1-year follow-up, pain status alteration, number of analgesics required, ankle–brachial index (ABI) change, compliance with supervised smoking cessation, and amputation-free rate were recorded. The pain status improved considerably according to a visual analog scale, the number of analgesics required was significantly reduced, and all patients improved their pain-free walking distance, the ABI, and their self-reported quality of life. Only 2 patients required minor amputations. Combination of IV Ilomedin infusion, supervised smoking cessation, and a specific follow-up protocol may lead to improvement in pain-free walking distance, pain status, quality of life, and substantial reduction in amputation risk.